2015
DOI: 10.1111/ahg.12116
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Sequence Variants in the NPR2 Gene Underlying Acromesomelic Dysplasia Maroteaux Type (AMDM) in Consanguineous Families

Abstract: SummaryAcromesomelic dysplasia Maroteaux type (AMDM) is an autosomal recessive skeletal disorder characterized by disproportionate short stature with shortening of the acromesomelic sections of the limbs. AMDM is caused by mutations in the NPR2 gene located on chromosome 9p21-p12. The gene encodes the natriuretic peptide receptor B (NPR-B) that acts as an endogenous receptor for C-type natriuretic peptide (CNP). Both CNP and NPR-B are considered as important regulators of longitudinal growth. The study present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
(37 reference statements)
0
11
0
2
Order By: Relevance
“…Genomic DNA was extracted from peripheral blood samples following standard procedures. Using microsatellite markers (Table SI), linkage was evaluated at four previously described syndromic and six non‐syndromic PAP loci ( ZNF141/PAPA1 , PAPA2 , PAPA3 , PAPA4 , PAPA5 , PAPA6 , PAPB , AHI1 , TMEM231 , ZNF423 , RPGRIP1L ) as described Irfanullah et al [].…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from peripheral blood samples following standard procedures. Using microsatellite markers (Table SI), linkage was evaluated at four previously described syndromic and six non‐syndromic PAP loci ( ZNF141/PAPA1 , PAPA2 , PAPA3 , PAPA4 , PAPA5 , PAPA6 , PAPB , AHI1 , TMEM231 , ZNF423 , RPGRIP1L ) as described Irfanullah et al [].…”
Section: Methodsmentioning
confidence: 99%
“…In humans, overexpression of CNP results in overgrowth [42, 43]. Conversely, homozygous inactivating mutations in natriuretic peptide receptor 2 ( NPR2 ), the primary receptor for CNP, cause acromesomelic dysplasia, Maroteaux type [44], whereas heterozygous mutations can present as idiopathic short stature with no or only subtle signs of a skeletal dysplasia [45, 46]. In 2 recent studies of idiopathic short stature, cohorts identified heterozygous NPR2 mutations in 0–6% of the patients [47, 48].…”
Section: Molecular Mechanism Involved In Longitudinal Growthmentioning
confidence: 99%
“…Acromesomelic dysplasias is a pathological condition during development during which skeletal elements under goes disproportionate shortening and usually middle parts of the forearms and legs are more affected (Bartels et al 2004 ; Irfanullah et al 2015 ). Acromesomelic dysplasia has three reported sub types based on phenotypic and radiological variations recorded in the patients: type Grebe (AMDG) (MIM #200700) (Umair et al 2016 ), type Hunter and Thompson (AMDH) (MIM #201250) (Ullah et al 2018 ) and Maroteaux type (AMDM) (MIM #602875) (Bartels et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%